Eksistensi Komisioner Perempuan dalam Mewujudkan Kesetaraan Gender pada Komisi Pemilihan Umum di Provinsi Sumatera Barat - Irma Novita; Jendrius Jendrius; M Fachri Adnan (Universitas Muhammadiyah Ponorogo, 2019)
This study examines the existence of female commissioners to increase gender equality in the General Election Commission in West Sumatra. The existence of female commissioners as election organizers is not only a matter of equality with men, but also will play a major role in efforts to encourage female political participation by maximizing female participation in elections both as voters, election participants, and as election organizers. The main act women can take as election organizers at each stage is to ensure that female needs are considered and incorporated into programs or policies that are properly designed and implemented. The research method used in this research is qualitative emphasizing the gender aspect more precisely feminist research (feminism research). The results of the number of female commissioners as election organizers are still minimal quantitatively. And if you look at the composition of the current membership structure, this female commissioners is still very minimal due to the 30 percent quota has not been fulfilled so there is still discrimination and many obstacles and challenges are found to increase gender equality and female opportunities are limited in performing the tasks of elections. Most of these commissioners also feel there is still gender inequality. Challenges and obstacles such as social barriers in the form of Patriarchal Culture that still exist in Minangkabau society are still felt even though it is not as thick as in past times. In addition, stereotypes, marginalization, subordination, and the double burden also greatly affect the existence of female commissioners to increase gender equality.